Program Pendampingan Debat Bahasa Inggris Bagi Siswa SMA Di Palangka Raya - Emeral, Emeral; Adji, Tegar Sukma; Tirtayasa, Tirtayasa; Loren, Teresya; Setiawan, Tenlie; Sylvanus, Tio (STMIK Royal, 2025)
The National Schools Debating Championship (NSDC) is among the most popular debate competitions. Schools in Indonesia strive to prepare their best students for this prestigious competition. One high school in Palangka Raya, Central Kalimantan, also prepares its students to participate in this prestigious event. To this end, the school formed an English Debate Club (EDC). However, the enthusiasm of EDC members in practising tends to be inconsistent, which impacts the effectiveness of their preparation. In response to this problem, a team of lecturer and students from the English Education Study Program, Palangka Raya University, implemented a coaching program to increase the enthusiasm, confidence, and debating skills of EDC members. The coaching activities were conducted in four sessions, covering motion analysis training, case studies, and debate practice, with guidance from an outstanding student representing the university in the National University Debating Championship (NUDC) at the national level. Qualitative questionnaire results indicated increased enthusiasm and self-confidence among EDC members during training sessions and improved understanding of debate strategies. This initiative demonstrates that coaching based on the direct experience of a high-achieving debater can serve as an effective strategy for developing debate clubs in secondary schools.Keywords: enthusiasm; coaching program; debate strategy; self-confidence; debate club Abstrak: National Schools Debating Championship (NSDC) merupakan salah satu kompetisi debat yang paling populer. Sekolah di Indonesia berusaha mempersiapkan potensi terbaiknya untuk mengikuti kompetisi bergengsi ini. Salah satu sekolah menengah atas di Palangka Raya, Kalimantan Tengah, juga mempersiapkan para siswanya untuk mengikuti ajang bergengsi tersebut. Untuk itu, sekolah membentuk English Debate Club (EDC). Namun, antusiasme anggota EDC dalam berlatih cenderung tidak konsisten, yang berdampak pada efektivitas persiapan mereka. Menanggapi permasalahan tersebut, tim dosen dan mahasiswa dari Program Studi Pendidikan Bahasa Inggris, Universitas Palangka Raya melaksanakan program pendampingan guna meningkatkan antusiasme, percaya diri dan kemampuan debat para anggota EDC. Kegiatan pendampingan dilakukan dalam empat sesi pertemuan, yang mencakup pelatihan analisis mosi, pembedahan kasus, serta praktik debat, dengan bimbingan dari mahasiswa berprestasi yang pernah mewakili universitas dalam ajang National University Debating Championship (NUDC) tingkat nasional. Hasil survei menunjukkan peningkatan antusiasme dan kepercayaan diri anggota EDC dalam mengikuti latihan, serta pemahaman yang lebih baik terhadap strategi debat. Kegiatan ini menunjukkan bahwa pendampingan berbasis pengalaman langsung dari mahasiswa debat berprestasi dapat menjadi strategi efektif dalam membina klub debat di sekolah menengah.Kata kunci: antusiasme; program pendampingan; strategi debat; percaya diri; klub debat